Manajemen Pasien dengan Hoarseness Paskatiroidektomi Total Dipacu - Kusuma, Danur Adi; Pratomo, Bhirowo Yudo; Jufan, Akhmad Yun (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2022)
look at the clinical appearance of the patient who appears hoarse after extubation, thevoice becomes softer, the ability to cough is not strong but the respiration rate is stillnormal 18 times/minute with a saturation of 98% then The probability of injury isunilateral. Pathophysiologically hoarseness can mean there is a possibility of injury toeither the bilateral superior laryngeal nerve or unilateral recurrent laryngeal nerve (RLN).Then the possibility of injury is unilateral RLN unilateral in this patient. Ideally thedifferential diagnosis of postoperative hoarseness requires examination such as simplelaryngoscopy, stroboscopy or intra and extralaryngeal electromyography. In practice it isdifficult to distinguish between damage caused by thyroid surgery and anaestheticfactors. There are a number of anesthetic-related factors that may predispose to hoarseness in these patients such as the risk of doubling in patients who are intubated for3-6 hours (in patients 3.5 hours). This could be ruled out if we could measure the ET cuffpressure during surgery. While from the surgical factor there are several risk factors suchas surgery on the neck area (thyroid surgery), excessive neck extension during surgery,pulling the RLN causing injury. In the last operation the position of the neck extended, forRLN in the operation report has been identified. It is better to assess vocal cord functionprior to extubation, such as a cuff leak test or insertion of a flexible intubation scopethrough the lumen of the ET tube.